Population of Kosovo during 16th – 17th Centuries: Array - Tetaj, Luan (Journal of Danubian Studies and Research, 2020)
The research paper is focused on the population status during the first centuries of Ottoman ruling in Kosovo. Archaeological, historical, linguistic and folklore data scientifically argue on the lineage of the Illyrian-Albanian during ancient times, the early Middle Ages in the territory of Kosovo, on the presence and predominance of the Albanian population during the Ottoman occupation between 15th -17th centuries. Opinions of Albanian and foreign historiography objectively and scientifically confirm the life continuation of Kosovo people in the areas where they live today.